Innovative delivery mechanisms for increased aid budgets: Lessons from a new Australian aid Partnership - Matthew Clarke (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
The Australian government will double its Official Development Assistance by 2015 (over 2010 levels). Innovative delivery mechanisms will be required to ensure aid is spent efficiently. In addition to traditional delivery mechanisms - bilateral, multilateral - the Australian government has piloted a small partnership activity with churches in the Pacific. The Church Partnerships Programme is premised on the realization that in certain Pacific countries, the churches have existing, functioning and well-regarded national networks and close links with local communities that are suitable conduits for donor funding. In this sense they are ideal partners for the delivery of effective aid. This paper will consider this model and the benefit it brings. There are of course consequences for both the churches and their communities for this influx of aid money and changing activities and these will be briefly considered. Finally, extending this partnership model to non-Christian religious faiths in other countries, such as Islamic nationwide organizations in Indonesia, is also discussed.
Keywords: O19; 330; development; religion; aid effectiveness; absorptive capacity; Papua New Guinea